Role of labour force (thozhil sena) in agricultural development implemented through people's plan in Kerala - Geetha Nath G (Department of Agricultural Extension, College of Agriculture, 2002)
The study entitled "Role of labour force (Thozhil Sena) in agricultural development implemented through people's plan was undertaken to study the structure, function and role of Thozhil Sena. It was also aimed to study the employment generation and income generation due to the implementation of Thozhil Sena, to study the attitude and perception of its members and farmers towards it and to identify the constraints as perceived by the mem bers/officials/people' s representatives. The study was conducted In Kunnathukal Panchayat of Thiruvananthapuram district and Thamarakulam Panchayat of Alapuzha district. A sample of 200 respondents were selected at random, which included 50 members of each Thozhil Sena and 50 farmers from each panchayat, who had the services of Thozhil Sena. Thirty respondents which included officials/members/people's representatives were selected from each panchayats to study the constraints. Data were collected through well structured and pretested interview schedule. The study shows that in Kurmathukal panchayat both members and farmers agreed that Thozhil Sena fulfilled majority of the roles listed out and they had a favourable attitude and high level of perception when compared to Thamarakulam Thozhil Sena.